Metal‐Free Atom Transfer Radical Polymerization of Methyl Methacrylate with ppm Level of Organic Photocatalyst. Issue 10 (28th October 2016) - Huang, Zhicheng; Gu, Yu; Liu, Xiaodong; Zhang, Lifen; Cheng, Zhenping; Zhu, Xiulin
Abstract : It is well known that the recently developed photoinduced metal‐free atom transfer radical polymerization (ATRP) has been considered as a promising methodology to completely eliminate transition metal residue in polymers. However, a serious problem needs to be improved, namely, large amount of organic photocatalysts should be used to keep the controllability over molecular weights and molecular weight distributions. In this work, a novel photocatalyst 1, 2, 3, 5‐tetrakis(carbazol‐9‐yl)‐4, 6‐dicyanobenzene (4CzIPN) with strong excited state reduction potential is successfully used to mediate a metal‐free ATRP of methyl methacrylate just with parts per million (ppm) level usage under irradiation of blue light emitting diode at room temperature, using ethyl α‐bromophenyl‐acetate as a typical initiator with high initiator efficiency. The polymerization kinetic study, multiple controlled "on–off" light switching cycle regulation, and chain extension experiment confirm the "living"/controlled features of this promising photoinduced metal‐free ATRP system with good molecular weight control in the presence of ppm level photocatalyst 4CzIPN. Abstract : A novel photocatalyst 1, 2, 3, 5‐tetrakis(carbazol‐9‐yl)‐4, 6‐dicyanobenzene is successfully used to mediate a metal‐free atom transfer radical polymerization of methyl methacrylate just with ppm level usage under irradiation ofa blue light emitting diode at room temperature.